Analisis Pengaruh Motivasi Intrinsik Dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan Pada Kantor Pelayanan Pajak Pratama Surakarta - Yuliantini, Puspa; , Ihwan Susila, S.E., M.Si., Ph.D (2017)
This study aims to analyze the influence of intrinsic motivation and extrinsic motivation on employee performance at Tax Office Pratama Surakarta. Based on the results of this study is expected to be useful as a benchmark and evaluation materials to provide a decision and new policies at the Tax Office Pratama Surakarta. Hypothesis testing in this research using moderating regression analysis tool with t test, F test and coefficient of determination (R 2 ). The population of this study is all employees at the Tax Office Pratama Surakrata. The sample in this research is 80 employees at Tax Office Pratama Surakrata. Based on the results of the research note that intrinsic motivation significantly influence the performance of employees KPP Pratama Surakarta, so H 1 accepted. Extrinsic motivation has a significant effect on the performance of KPP Pratama Kota Surakarta employees, so that H 2 is accepted. Keywords: intrinsic motivation, extrinsic motivation, employee performance.